Structural analysis and optimization of an advanced all-GFRP highway bridge. (December 2021) - Wang, Jinxiao; Cheng, Bin; Yan, Xingfei; Zhang, Kailong; Zhou, Zhenxing
Abstract: In this research, a relative novel type of composite structure for a glass fiber reinforced polymer (GFRP) highway bridge was analyzed that consisted of a multi-cell GFRP deck and two U-shaped GFRP girders, and the structural analysis and optimization of such advanced structure was presented. The deformation mechanism was analyzed using theoretical formulations. It was found that the deformation was mainly composed of flexural deformation rather than shear deformation. By employing laminated shell elements, a finite element (FE) analysis was carried out to investigate the structural behaviors of the bridge structure for various load cases. The results indicate that the structural indexes including the deflection, stress, dynamic frequency, and anti-overturning stability all met the requirements of the design code. By using the zero-order optimization method, the multi-parameter structural optimization was further conducted to obtain the minimum weight of the structure, in which four sectional parameters of the girder (i.e., top flange thickness, bottom flange thickness, web thickness, and girder depth) were considered the design invariables. The optimal structural schemes for various combinations of design variables were obtained. The results revealed that the thinner the top flange and the web were, or the thicker the bottom flange was, the lighter the optimized structure was. The achievements verified the applicability of such composite GFRP structures for highway bridges.